Postpartum decline in sflt-1/plgf ratio confirms placental source of angiogenic imbalance and endothelial dysfunction in preeclampsia - Samardjiski, Igor; Simeonova Krstevska, Slagjana; Livrinova, Vesna; Irena Todorovska; Paneva, I.; Joksimovic, Marija; Atanasova Boshku, Aleksandra (Elsevier BV, 2024)
Preeclampsia (PE) is a multisystem disorder in pregnancy with a specific collection of signs and symptoms as a result of serious dysfunction of multiple organs. Abnormal placentation in the first trimester, most likely triggers the disbalance of the placental anti-angiogenic factor soluble fms-like tyrosine kinase-1(sFlt-1) and pro-angiogenic placental growth factor (PlGF), which result in systemic endothelial dysfunction (injury) to progressive end-organ damage. According the PROGNOSIS study, the cut-off value of the sFlt-1/PlGF ratio over 85 confirms the suspected PE and proved to be useful in preeclampsia diagnosis. A severely elevated sFlt-1/PlGF ratio is associated closely with the need to deliver within 48hours.